The Monitoring of Filamentous Fungi in the Indoor Air Quality, and Health - Sahu1; Kiran Pandey4, U. Kutti1, Sushma Dubey3*, S. Lanjewar2, Motilal (Journal of Phytology, 2011)
<span style="font-size: 10pt; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;">The air we breathe is essential for life, yet at the same time it is a potential source of contaminants associated with disease. Fungal spores are among the most common airborne bioparticles in air and play an important role in biodeterioration, allergy and many diseases, their concentration and types depend on the environmental parameters, types of vegetation and source of contamination. In this one year survey it was observed that the maximum no. of fungal species was recorded in winter season because of Temperature, Relative humidity and Rainfall favourable for fungal growth (28±1Ã¢â€”Â¦ C and R.H. 88%) and minimum no. of fungal species were recorded in summer season because high Temperature and low R.H. and very dry air not favourable for growth of fungal species. The results provide to be helpful to allergologist and clinician in treatment of fungal related disease. This article aims to update current scientific knowledge concerning the health effects of exposure to fungi in indoor air, since most complaints with microbial contamination of indoor air involve this type of microorganism.